Comments on 'Selective evolution of secondary γ′ precipitation in a Ni-based single crystal superalloy both in the γ matrix and at the dislocation nodes'. (1st March 2017) - Cormier, Jonathan; Caccuri, Vincenzo; le Graverend, Jean-Briac; Villechaise, Patrick
Abstract: In a recent paper, Sisi Xiang & al. [Acta Materialia 116 (2016) 343] studied microstructure evolutions of γ′ precipitates during creep of a Ni-based single crystal superalloy, with a special focus on hyperfine γ′ particles nucleating in the γ matrix channels. This paper is misleading, claiming that hyperfine γ′ particles nucleate during high temperature creep exposure at 1100 °C. The aim of the present comments is to reconsider these results based on the available literature on hyperfine γ′ particles nucleation mechanisms and subsequent morphological evolutions at high temperature.